2015
DOI: 10.1055/s-0034-1398949
|View full text |Cite
|
Sign up to set email alerts
|

Abdominelle Sonografie bei Patienten mit Diabetes mellitus. Teil 1: Leber

Abstract: In patients with diabetes mellitus, abdominal ultrasonography is the appropriate diagnostic technique to detect and to follow-up secondary and accompanying diseases of the liver, the kidneys, the pancreas, the gastrointestinal tract and of abdominal vessels. Moreover, pancreatic and hepatic diseases may be realized which are of etiological importance for diabetes mellitus. Based on a systematic survey of the published literature, this review in 3 parts will describe the value of abdominal ultrasonography in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 183 publications
0
2
0
1
Order By: Relevance
“…The following abdominal organs were evaluated and listed on-site findings as previously described [2]: 1) liver: focal liver lesion detection [44][45][46][47] including focal fatty sparing [48,49]; portal vein (flow direction)…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…The following abdominal organs were evaluated and listed on-site findings as previously described [2]: 1) liver: focal liver lesion detection [44][45][46][47] including focal fatty sparing [48,49]; portal vein (flow direction)…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…It has been shown that the presence of NAFLD diagnosed by US is independently associated with an increased prevalence of ischemic heart disease [118,119]. The SHIP study, a large population-based study in Northern Germany, showed in a 5-and 10year follow-up that patients with a fatty liver had significantly higher morbidity and mortality than patients without this condition [120,121,122].…”
Section: Us Detection Of Nafld As a High-risk Constellation For Ather...mentioning
confidence: 99%
“…5], bestimmten Krankheiten (z. B. Diabetes mellitus)[57], Point-of-care-Ultraschall (sei es innerhalb oder außerhalb des Krankenhauses)[3, 4, 58 -60] und vieles andere mehr. Dank technischem Fortschritt und Kostenreduktion der Ultraschallgeräte ermöglicht die Nutzung kleiner, tragbarer Ultraschallgeräte dem Arzt, den Patienten im häuslichen Umfeld zu untersuchen und gegebenenfalls weitere diagnostische und therapeutische Schritte in die Wege zu leiten.…”
unclassified